HemU and TonB1 contribute to hemin acquisition in Stenotrophomonas maltophilia - Liao, Chun-Hsing; Lu, Hsu-Feng; Yang, Ching-Wei; Yeh, Ting-Yu; Lin, Yi-Tsung; Yang, Tsuey-Ching (Frontiers in Cellular and Infection Microbiology, 2024)
The hemin acquisition system is composed of an outer membrane TonB-dependent transporter that internalizes hemin into the periplasm, periplasmic hemin-binding proteins to shuttle hemin, an inner membrane transporter that transports hemin into the cytoplasm, and cytoplasmic heme oxygenase to release iron. Fur and HemP are two known regulators involved in the regulation of hemin acquisition. The hemin acquisition system of Stenotrophomonas maltophilia is poorly understood, with the exception of HemA as a TonB-dependent transporter for hemin uptake. Methods: Putative candidates responsible for hemin acquisition were selected via a homolog search and a whole-genome survey of S. maltophilia. Operon verification was performed by reverse transcription-polymerase chain reaction. The involvement of candidate genes in hemin acquisition was assessed using an in-frame deletion mutant construct and iron utilization assays. The transcript levels of candidate genes were determined using quantitative polymerase chain reaction.Results: Smlt3896-hemU-exbB2-exbD2-tonB2 and tonB1-exbB1-exbD1a-exbD1b operons were selected as candidates for hemin acquisition. Compared with the parental strain, hemU and tonB1 mutants displayed a defect in their ability to use hemin as the sole iron source for growth. However, hemin utilization by the Smlt3896 and tonB2 mutants was comparable to that of the parental strain. HemA expression was repressed by Fur in iron-replete conditions and derepressed in iron-depleted conditions. HemP negatively regulated hemA expression. Like hemA, hemU was repressed by Fur in iron-replete conditions; however, hemU was moderately derepressed in response to iron-depleted stress and fully derepressed when hemin was present. Unlike hemA and hemU, the TonB1-exbB1-exbD1a-exbD1b operon was constitutively expressed, regardless of the iron level or the presence of hemin, and Fur and HemP had no influence on its expression.HemA, HemU, and TonB1 contribute to hemin acquisition in S. maltophilia. Fur represses the expression of hemA and hemU in iron-replete conditions. HemA expression is regulated by low iron levels, and HemP acts as a negative regulator of this regulatory circuit. HemU expression is regulated by low iron and hemin levels in a hemP-dependent manner.